Perencanaan Website Peta Tata Wilayah Untuk Kebutuhan Infrastruktur Dan Penunjang Fasilitas Pelayanan - Valentino Gracia Lumban Tobing; Melia Putri Ivana; Stevenson Ari Kuswandi; Haris Setyawan; Reynald Marcelinovanto; Denny Denny; Maryanto Maryanto (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
Pahandut Village in Palangka Raya City, Central Kalimantan, is experiencing rapid socio-economic growth, requiring accurate spatial data support for regional planning and management. Until now, the availability of spatial information at the Rukun Tetangga (RT) level, especially related to regional boundaries, infrastructure conditions, and the location of public facilities, is still limited and has the potential to hinder the process of formulating development needs. The Building and Impact Engineering (TMB) program activities are carried out to help overcome these problems through the preparation of spatial databases of urban villages. The implementation process uses qualitative and quantitative approaches, through field surveys and interviews to obtain data on RT/RW boundaries and public facilities. The collected data is then digitally processed using QGIS software, so that spatial information can be converted into digital maps and compiled in a geospatial format. The results of the visualization are then integrated into the website platform to facilitate access and utilization of information. The output of the activity is in the form of a website-based digital map that can be a more structured, accurate, and effective source of spatial data to support development decision-making in Pahandut Village